Perspektif Kepala Sekolah dan Guru tentang Tunjangan Sertifikasi terhadap Kinerja di SMA 1 Teluk Gelam - Wiwin Triani; Indriah Juwita; Mila Meiyanti; Neta Dian Lestari; Ahmad Zulinto; Musfirowati Musfirowati (CV. Ulil Albab Corp, 2026)
This study aims to explore the perspectives of principals and teachers regarding the impact of certification allowances on performance at SMA Negeri 1 Teluk Gelam. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with the principal and several teachers who had received certification allowances. The results show that certification allowances are considered to provide additional motivation for teachers to improve their performance. Teachers feel more appreciated and enthusiastic about developing more effective teaching methods. In addition, this allowance encourages increased professionalism and responsibility in carrying out duties. However, there is also a view that this allowance should be accompanied by stricter performance evaluations to ensure a sustainable positive impact. Overall, certification allowances play a significant role in improving the quality of education, although challenges in their implementation need to be continuously evaluated. These findings can serve as a basis for better education policies in optimizing the benefits of certification allowances.